Designing A Service Registration System at AHHAS Honda Ilham Motor Kepahiang - Aji Setiyadi; Anisya Sonita; Yulia Darnita; A.R Walad Mahfuzhi (Penerbit Jurnal Indonesia, 2025)
In the automotive world, organized and efficient service registration services are very important to support workshop operations and improve customer satisfaction. This process includes recording customer data, service schedules, and the types of services required, so a system design is needed that can serve the motor vehicle service registration process and make it easier for customers to service their vehicles. This study aims to design and develop a digital-based service registration system prototype at AHHAS Honda Ilham Motor Kepahiang. The system is designed to replace the manual registration method previously used, which often caused long queues and inefficiency in managing service schedules. With this prototype, customers can register for service online, choose available schedules, and receive automatic confirmation notifications. The system also includes features for managing customer data and vehicle service history, which help the workshop improve operational efficiency. The implementation of this prototype is expected to provide a more comfortable experience for customers and support the workshop in addressing challenges in the digital era